Evaluation of the Suitability of Bend Geometry on Road User Perceptions: Case Study of Bantrangsana Bend on Jalan Raya Siliwangi Majalengka - Yusan Nurul Septiyani; Ade Jaya Saputra (Fakultas Teknik Sipil dan Perencanaan, 2024)
Road geometric factors, such as curve design, have significantly contributed to traffic accidents. Inappropriate corner design can cause the vehicle to lose control, especially at high speeds. Road geometry plays an important role in traffic safety, with many studies showing that poor geometric design can increase the risk of accidents. In Indonesia, evaluating road geometry is the main focus in improving traffic safety. In Indonesia, evaluating road geometry is the main focus in improving traffic safety. This research focuses on the Bantrangsana corner on Jalan Raya Siliwangi, Majalengka, because it is often reported as a location with a high accident rate. This research aims to evaluate the suitability of bend geometry to the perception of road users at the Bantrangsana Bend on Jalan Raya Siliwangi Majalengka using the Interpretative Phenomenological Analysis (IPA) approach. Results with 20 road users revealed that corner visibility is poor at night. When it rains, the narrow road width adds discomfort, especially when facing vehicles from the opposite direction, in traffic jams or vehicles leaving the road connecting to Bantrangsana village. Also, at the Bantrangsana bend, a road connects to Bantrangsana village; it can be seen on the location plan that the bend is a bend with a T-junction. Therefore, additional improvements are needed, such as improving lighting, adjusting road width, and adding clearer signs to improve the safety and comfort of road users at Bantrangsana Bend. The results of this study demonstrate the importance of considering road user perceptions in evaluating and designing road geometry to ensure a safer and more comfortable driving experience.